2019
DOI: 10.4314/ajcem.v20i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of methicillin resistance and virulence genes of <i>Staphylococcus aureus</i> with infection types and mode of acquisition in Sofia, Bulgaria

Abstract: Background: Infections due to methicillin resistant Staphylococcus aureus (MRSA) which is the most virulent species among the staphylococci have become a global health challenge. The aim of this study was to assess the correlation of genes encoding virulence and methicillin resistance in invasive and non-invasive isolates from inpatients/outpatients with staphylococcal infections in Sofia, Bulgaria. Materials and methods: Non-duplicate S. aureus isolates were recovered from clinical samples obtained from a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Our study reported a higher prevalence of the tst gene among MRSA than MSSA. This finding is in tandem with reports made in similar studies where an association was observed between methicillin resistance and the prevalence of the tst gene [20,31]. Other similar studies have reported an insignificant association between methicillin sensitivity and prevalence of the tst gene [19,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Our study reported a higher prevalence of the tst gene among MRSA than MSSA. This finding is in tandem with reports made in similar studies where an association was observed between methicillin resistance and the prevalence of the tst gene [20,31]. Other similar studies have reported an insignificant association between methicillin sensitivity and prevalence of the tst gene [19,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…We found that SEs genes were more frequent among MRSA than MSSA strains. Other studies also showed a significant association between methicillin resistance and the presence of the majority of SEs genes [ 5 , 21 , 36 , 42 , 52 ]. In our study, among the tested genes encoding enterotoxins tested, only sea was found in more MSSA strains than MRSA.…”
Section: Discussionmentioning
confidence: 93%
“…PCR was performed in a 25 mL reaction mix. All phenotypically and biochemically determined S. aureus strains were again genetically confirmed by PCR assay using species-specific genes: Sau 327 and Sau 1645 23S rRNAas described previously [8]. Twelve virulence determinants (hlg, sea, seb, sec, sed, see, seg, seh, sei, sej, tst, can) were detected based on the previously described protocols [8].…”
Section: Polymerase Chain Reaction (Pcr) Assaymentioning
confidence: 99%
“…Cumulative effects of many extracellular products which can play a role in pathogenesis are associated with the burden and clinical manifestations of staphylococcal infections. It is an etiological agent of both community acquired (CA) and nosocomial, healthcare-associated (HA) infections in humans [7][8][9][10][11]. The HA infections due to staphylococcal colonization of intravascular catheters and orthopedic devices causes significant patient morbidity and mortality worldwide [1,2,4].…”
Section: Introductionmentioning
confidence: 99%